Perancangan Aplikasi Penjualan Vast Hijab Tangerang Menggunakan Metode Waterfall - Ade Dewa; Alvinda Shahrul; Husaini Lutfi; Thoyyibah. T (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Designing the Tangerang Vast Hijab Sales Application Using the Waterfall Method. Informatics Engineering Study Program, Pamulang University Engineering Study Program. The use of this Sales System Application is to provide convenience to users and customers. Therefore it is necessary to make a Sales System application to improve the performance process at the Store which was originally manual to be computerized. The purpose and making of this application is to provide facilities for customers and companies to introduce the Vast Hijab Store, through a website that has complete features such as (1) a web-based application program that contains complete information from the Vast Hijab Store; (2) the existence of a product catalog that contains details of the production results. In addition, it is hoped that this website can help customers get to know Vast Hijab Store and the products offered.